Biodiversitas Lumut Epifit di Gunung Kendeng Dalam Kawasan Taman Nasional Gunung Halimun Salak Jawa Barat - Giry Marhento; Chisma Zaenab (The Ethnobiological Society of Indonesia, 2021)
The purpose of this study was to obtain information on the number of types of epiphytic moss in the Kendeng Mountains in the Halimun Salak Mountain National Park, West Java and to determine the function of epiphytic moss as an environmental bio-indicator. The research method used is descriptive qualitative by means of primary data collection through observation and interviews, while secondary through documentation. The results of research conducted in the area of Mount Halimun Salak National Park, there are 16 species. The types found at the two stations are classified into 14 tribes. The epiphytic moss substrate in the Halimun Salak Mountain National Park is on weathered logs and tree bark. The type of epiphytic moss (Bryophytes) in the Halimun Salak Mountain National Park which has the highest importance is Fissindens viridulus with a value of 48.9. The type of moss with the lowest importance is Scapania sp. with a value of 1.72. The diversity of moss in the Mount Halimun Salak National Park area is 2,149. The diversity index value in the Mount Halimun Salak National Park area is included in the moderate category, because it has a value of 1≤ Ĥ ≤ 3.The diversity of moss species (Bryophytes) on various substrates found in the Mount Halimun Salak National Park area is moderate, both on terrestrial substrates. (diversity index value 1.276) and arboreal (diversity index value 1.851). This shows that the diversity of arboreal substrates is higher than terrestrial. The physical form of moss is used as an environmental indicator and also for gardening and greenhouses. Another thing that has been done with this moss is to use it as a medicinal ingredient.